Apollinaire et le Cubisme. - Palais des Beaux-Arts, Lille; Apollinaire, Guillaume; Chevalier, Jean-Claude; Châtelet, Albert; Decaudin, Michel; Durry, Marie-Jeanne (Lille : Palais des Beaux-Arts Lille, 1965)
Picasso, Pablo ; Braque, Georges ; Delaunay, Robert ; Terck-Delaunay, Sonia ; Duchamp, Marcel ; Duchamp-Villon, Raymond ; Efrat, Serge ; Gleizes, Albert ; Gris, Juan ; Fresnaye, Roger de la ; Laurencin, Marie ; Leger, Fernand ; Marcoussis, Louis ; Metzinger, Jean ; Picabia, Francis ; Severini, Gino ; Villon, Jacques
Apollinaire et le cubisme, Palais des Beaux-Arts, Lille, 3 Avril - 4 Mai 1965
biografie
Frans
boek